Searching for Islamic Economics: A Philosophical Inquiry - Syamsuddin Arif (Journal of Critical Realism in Socio-Economics (JOCRISE), 2023)
All science is mirroring a Weltansicht, or worldview‒that is, a comprehensive framework through which individuals or cultures interpret and understand the world around them. Worldviews not only provide a broader context for interpreting the data, but also influence research directions, methodological preferences, and final conclusions. Economics is no exception to this phenomenon. This modest essay aims to open up the epistemological foundations of modern economics to closer scrutiny with a view to pinpointing the tacit assumptions, cultural or other biases, and preconceived notions operating beneath the surface of economic theories, models, methods, and approaches. In addition, this essay also explores the controversial idea of Islamic economics which its exponents say recognizes the interdependence between economic outcomes and ethical choices, and take into account the importance of aligning economic activities with universally accepted human values.